PASAR MODAL DALAM PERSPEKTIF ISLAM - Romansyah, Romansyah (IAIN Samarinda, 2015)
Capital Markets are long enough to be known by the entrepreneurs and the investors in an effort to expand their businesses or by that of speculators simply for looking for great profits. The Indonesian capital markets are supervised by BAPEPAM in order to prevent illicit transactions that include window dressing. The capital markets may operate through the primary market, secondary market, third market and fourth market; yet, only the primary market that is expected to run in accordance to shari'a. This is because the issuers directly offer their shares or securities to prospective buyers or potential investors without going through the brokers’ services. This article is thus to analyses this primary market option from the Islamic law point of view.